An in Silico Approach to Find the Molecular Targets and Potential Candidates for SARS-CoV-2 - Amir Zarrinhaghighi; Ali Dehshahri (Shiraz University of Medical Sciences, 2020)
The rapid spread of SARS-CoV-2 has led researchers to seek novel drugs as well as re-purposing the existing drugs to prevent control or treat COVID-19. An interesting approach is to focus on the molecular pathways which could act as a drug target in this disease. Since the molecular pathways associated with SARS-CoV-2 are still unclear, the SARS-CoV infected patients and the convalescent individuals were selected as the model for SARS-CoV-2 infection and an in silico study was designed to identify the potential pathways which could act as the target for drug molecules. In the next step, the drugs with the ability to target these pathways were selected and introduced as potential compounds for further investigations to finding a drug for COVID-19. The results revealed that lycorine and GW-5074 are two small molecules with the ability to target the selected pathways. Interestingly, these compounds had shown antiviral activity against a broad range of viruses, including SARS-CoV. The results obtained in this in silico study could be considered as a primary study for further investigations.